2012
DOI: 10.3109/09513590.2012.685205
|View full text |Cite
|
Sign up to set email alerts
|

Differential insulin response to myo-inositol administration in obese polycystic ovary syndrome patients

Abstract: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, chronic anovulation, polycystic ovaries at ultrasound evaluation, and quite frequently by insulin resistance or compensatory hyperinsulinemia. Attention has been given to the role of inositol-phosphoglycan (IPG) mediators of insulin action and growing evidences suggest that a deficiency of D-chiro-inositol (DCI) containing IPG might be at the basis of insulin resistance, frequent in PCOS patients. On such basis, we investigated the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 27 publications
3
56
0
10
Order By: Relevance
“…Phosphoglycans formed by DChiro-Inositol seem to play a relevant role in insulin signaling transduction and seems to be more effective in partially restoring insulin sensitivity and glycogen synthesis than phosphoglycan incorporating Myo-Inositol [25]. Accumulating evidence suggests that Myo-Inositol could play a key role in improving hormonal and metabolic homeostasis in PCOS [26][27][28][29][30][31], assisted reproductive technology (ART) [32][33][34][35], and even in Gestational Diabetes Mellitus (GDM) [36][37][38][39]. Nevertheless, in PCOS patients, Myo-Inositol seems to have the most marked effect on the metabolic profile, whereas D-Chiro-Inositol reduces hyperandrogenism better [40].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoglycans formed by DChiro-Inositol seem to play a relevant role in insulin signaling transduction and seems to be more effective in partially restoring insulin sensitivity and glycogen synthesis than phosphoglycan incorporating Myo-Inositol [25]. Accumulating evidence suggests that Myo-Inositol could play a key role in improving hormonal and metabolic homeostasis in PCOS [26][27][28][29][30][31], assisted reproductive technology (ART) [32][33][34][35], and even in Gestational Diabetes Mellitus (GDM) [36][37][38][39]. Nevertheless, in PCOS patients, Myo-Inositol seems to have the most marked effect on the metabolic profile, whereas D-Chiro-Inositol reduces hyperandrogenism better [40].…”
Section: Introductionmentioning
confidence: 99%
“…16,[19][20][21] Minozzi et al found significant reduction from 9.7+3.6 to 6.7±1.9 (p<0.05) in Ferriman Gallwey score after 12 months therapy with 4gm Myoinositol plus 400µg folic acid in combination with OCP (EE 30 µg/gestodene 75 mg) and also shown significant reduction from 10.2+3.4 to 8.1+2.3 in group receiving OCP (EE 30 µg/gestodene 75 mg) alone but FG score was significantly lower in OCP+MYO+Folic acid group compared with OCP group (p<0.001). 19 Zacche et al found significant reduction from 11.4±3.2 to 9.94±2.8 in Ferriman Gallwey score after 6 months therapy with 2gm Myoinositol (p<0.05) and Le donne et al also observed significant reduction in Ferriman Gallwey score after 12 wks therapy with 4gm Myoinositol+Diet+metformin (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Genazzani et al [15] report an increase in the body mass index in patients with PCOS. These data were not confirmed in our study, the body mass index values in the groups were comparable.…”
Section: Discussionmentioning
confidence: 98%